2014
DOI: 10.1007/s11033-014-3527-5
|View full text |Cite
|
Sign up to set email alerts
|

Construction of transformed, cultured silkworm cells and transgenic silkworm using the site-specific integrase system from phage φC31

Abstract: The Streptomyces bacteriophage, φC31, uses a site-specific integrase enzyme to perform efficient recombination. The recombination system uses specific sequences to integrate exogenous DNA from the phage into a host. The sequences are known as the attP site in the phage and the attB site in the host. The system can be used as a genetic manipulation tool. In this study it has been applied to the transformation of cultured BmN cells and the construction of transgenic Bombyx mori individuals. A plasmid, pSK-attB/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recombination occurs at these pseudo-sites, because of their similarity in nucleotide sequence with the wild-type attP [167]. Pseudo-attP sites have been reported to be present not only in invertebrates [168,169], lower vertebrates [170], but also in mouse [163], human [167,171], cattle [172,173], sheep [174], goat [175] and pig [176] genomes. Accumulating experimental evidence indicates that these pseudo-target sites reside in genomic locations that conform to the definition of ''safe harbors'' [177,178].…”
Section: Application Of Site-specific Recombinasesmentioning
confidence: 99%
“…Recombination occurs at these pseudo-sites, because of their similarity in nucleotide sequence with the wild-type attP [167]. Pseudo-attP sites have been reported to be present not only in invertebrates [168,169], lower vertebrates [170], but also in mouse [163], human [167,171], cattle [172,173], sheep [174], goat [175] and pig [176] genomes. Accumulating experimental evidence indicates that these pseudo-target sites reside in genomic locations that conform to the definition of ''safe harbors'' [177,178].…”
Section: Application Of Site-specific Recombinasesmentioning
confidence: 99%
“…However, random insertions of exogenous sequences, resulting from the use of transposase‐mediated transformation systems, may cause unpredictable variations in gene expression and the undesirable mutagenesis of important genes (Labbe et al ., 2010). Furthermore, the recently developed site‐specific recombination systems, for the integration of exogenous genes into the silkworm genome mediated by the phiC31 integrase, provides an alternative that may overcome these problems (Long et al ., 2013; Yin et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The piggyBac transposon-based germline transformation technology has been extensively applied in functional analyses of B. mori genes and in the development of silkworms as bioreactors (Tamura et al 2000;Tomita et al 2003;Zhao et al 2010). In recent years, an increasing number of genetic manipulation tools have been used successfully in the silkworm, including the Minos transposon (Uchino et al 2007(Uchino et al , 2008, sitespecific recombinase (SSR) systems (Long et al , 2013Duan et al 2013;Yonemura et al 2013;Yin et al 2014), zinc finger nuclease (ZFN) (Takasu et al 2010;Ma et al 2014), transcription-activatorlike effector nuclease (TALEN) Shiomi et al 2015), and clustered regularly-interspersed short palindromic repeats-RNA-guided Cas9 nuclease Zeng et al 2016), to achieve random or site-specific integration of exogenous genes, knockout endogenous genes, and create large genomic deletions.…”
Section: Introductionmentioning
confidence: 99%
“…The recombination activity of these three recombinases has been demonstrated in B. mori in vivo (Long et al , 2013Duan et al 2013), and these SSR systems have many advantages for transgenic engineering that are lacking in transposonbased systems, including site-specific DNA excision mediated by FLP or Cre recombinase Duan et al 2013) and heritable, site-specific transgene integration mediated by the phiC31 integrase (Long et al 2013;Yonemura et al 2013;Yin et al 2014). Compared with genome-editing nucleases (ZFN,TALEN,and Cas9), the main advantages of SSR systems are that they can be used to achieve precise excision and integration of exogenous DNA fragments at pre-defined chromosomal sites in the silkworm, while genome-editing nucleases are primarily used to knockout endogenous genes (Takasu et al 2010;Wei et al 2014) and excise genomic DNA fragments from B. mori Wang et al 2013); previous studies showed that the efficiencies of ZFN-and TALEN-mediated, site-specific integration of exogenous DNA into the silkworm genome were very low Nakade et al 2014;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%